Fagoterapia en sistemas acuícolas: antecedentes y perspectivas (2021)
In context of the bacterial resistance crisis in the aquaculture industry and the need for alternatives to take on this obstacle, phage therapy appears as an alternative for prevention and treatment of bacterial diseases. Research focused on phage therapy in aquaculture systems has had an exponential growth in the last years, generating information that allows to mitigate the great economic losses derived from bacterial diseases. This review presents the state of the art of phage therapy for the control of diseases caused by bacteria in the aquaculture industry. The specific characteristics of bacteriophages, that play a key role in their application as therapy were analyzed, among them: phage specificity, bacterial resistance, reported phage diversity and their administration and stability. The study showed that although the number of research on the subject has increased, there are challenges associated with its scaling up and transfer to the productive sector. Despite the limitations, it was concluded that it is highly feasible to apply it successfully in aquaculture in the near future.